2008
DOI: 10.1021/cg070590d
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Polymorphism in Oxybuprocaine Hydrochloride

Abstract: The structural and thermodynamic features of three polymorphic forms of the local anesthetic drug oxybuprocaine hydrochloride (OBPHC) were characterized by hot-stage microscopy, differential scanning calorimetry (DSC), pycnometry, Fourier transform infrared spectroscopy (FTIR), FT-Raman and solid-state NMR (SSNMR) spectroscopy as well as X-ray powder and single-crystal diffractometry. Mod II°crystallizes in the space group P2 1 /n, is present in commercial products, and is the thermodynamically stable form at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The molecule adopts a strongly elongated shape. Due to its flexibility, one can expect the APZ molecule to adopt different conformations in its various solid state forms (conformational polymorphism8–10). However, as we have reported recently,11 it is also possible that distinct polymorphs of molecules with a high degree of molecular flexibility consist of conformers which are exactly the same.…”
Section: Introductionmentioning
confidence: 99%
“…The molecule adopts a strongly elongated shape. Due to its flexibility, one can expect the APZ molecule to adopt different conformations in its various solid state forms (conformational polymorphism8–10). However, as we have reported recently,11 it is also possible that distinct polymorphs of molecules with a high degree of molecular flexibility consist of conformers which are exactly the same.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular packing and hydrogen bonding in five polymorphs of sulfathiazole has been studied, and in this study, the approach used to compare packing geometries indicated that the degree of structural similarity was greater than had been previously thought 52. The conformational polymorphism existing in three crystal forms of oxybuprocaine hydrochloride has been investigated using a multi‐disciplinary approach, but even though a variety of molecular conformation were theoretically possible, only two basic types were found to exist in the three crystal forms 53. Crystal structures for the δ‐polymorph of sulphanilamide,54 as well as the δ and ε forms of chlorpropamide,55 have been reported.…”
Section: Structural Characterization and Properties Of Polymorphs Andmentioning
confidence: 96%
“…For example, basic 1D 13 C CP-MAS and CP-TOSS experiments have seen extensive application to the study of polymorphism in drugs over the past 15 years. 17,176,[183][184][185][186][187] In most applications, the appreciable chemical shift anisotropy (CSA) of many aromatic and carbonyl 13 C sites leads to a number of spinning sidebands that can complicate spectral interpretation, and thus either TOSS methods or MAS rates in the 12-15 kHz range are often employed when using B 0 fields in the range of 9.4-11.7 T. Using these techniques, 13 C CP-MAS or CP-TOSS spectra of most drug polymorphs offer excellent resolution, particularly at higher fields, and can readily discriminate between polymorphs with reasonable sensitivity using acquisition times of several hours. Well-known examples include prednisolone and its 21-tert-butylacetate ester, enalapril maleate, furosemide, cyclopentathiazide and sulfathiazole.…”
Section: 90mentioning
confidence: 99%
“…176,180,182,183 In these studies, 13 C spectra are often used to elucidate differences in hydrogen bonding or molecular conformation between polymorphs. 17,176,[183][184][185][186][187] Although most typical drug polymorphs of interest have reasonable 1 H T 1 values of 1-5 s, some smaller molecules have been known to exhibit very long 1 H T 1 values, which greatly reduces the sensitivity of 13 C CP experiments.…”
Section: 90mentioning
confidence: 99%